2023
DOI: 10.1038/s41598-023-29344-y
|View full text |Cite
|
Sign up to set email alerts
|

Novel biomarkers for neoplastic progression from ulcerative colitis to colorectal cancer: a systems biology approach

Abstract: In recent studies, the void of evaluation and in-depth understanding of unknown clinically relevant potential molecular biomarkers involved in colorectal cancer (CRC) from the inflammatory stage of ulcerative colitis (UC) to CRC metastasis, which can be suitable therapeutic targets, is deeply felt. The regulation and interaction among different cancer-promoting molecules, including messenger RNAs (mRNAs) and micro RNAs (miRNAs) in CRC and its progression, were the aim we pursued in this study. Using microarray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 60 publications
(65 reference statements)
0
4
0
Order By: Relevance
“…8 Kaplan-Meier plots demonstrating the relationship between HAND2-AS1 expression and overall survival (OS) in diverse cancers, highlighting significant outcomes. The pink line signifies high expression groups, while the black line corresponds to the low expression group prognosis of this disease [25][26][27]. In this study, the analyses identified 2299 genes, and by identifying the important interactions of lncRNA-mRNA, the Co-expression and regulatory network of mRNA-lncRNA in CRC has been investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Kaplan-Meier plots demonstrating the relationship between HAND2-AS1 expression and overall survival (OS) in diverse cancers, highlighting significant outcomes. The pink line signifies high expression groups, while the black line corresponds to the low expression group prognosis of this disease [25][26][27]. In this study, the analyses identified 2299 genes, and by identifying the important interactions of lncRNA-mRNA, the Co-expression and regulatory network of mRNA-lncRNA in CRC has been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon is especially pronounced in CRC and other malignancies [27]. Based on our team's previous studies aimed at identifying important biomarkers in CRC, we performed a comprehensive transcriptome analysis of lncRNA-mRNA interactions to identify further biomarkers that could aid in the diagnosis, treatment, and prognosis of this disease [28][29][30]. In this study, the analyses identi ed 2299 genes, and by identifying the important interactions of lncRNA-mRNA, the Co-expression and regulatory network of mRNA-lncRNA in CRC has been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The aim of our study was to identify, by miRNA profiling and subsequent bioinformatic validation, potential biomarkers of UC disease progression to colorectal cancer. Some microarray-based studies have identified gene expression profiles in UC and CRC [ 15 ]. Long-term inflammatory bowel disease increases the risk of CRC; thus, we enrolled patients with a UC disease for at least 10 years [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…1,2 However, these approaches are most effective when applied during the early stages of the disease. 3 While the 5-year survival rate for CRC patients is approximately 90% in the early stages, it drops below 5% in cases with distant metastases. 4 Limitations in the existing treatment strategies and CRC's high metastatic potential contribute to the detection of the disease at advanced stages, leading to an increase in mortality rates.…”
Section: Introductionmentioning
confidence: 99%